Kesan Suhu dan Kadar Terikan ke atas Sifat Regangan Komposit Getah Asli Tennoplastik (HDPE/NR) Berpenguat Gentian Karbon Pendek - Ahmad, Sahrim; Mohamed, Nor Hasimah (Universiti Putra Malaysia Press, 2000)
Thermoplastic natural rubber (TPNR) composite was prepared using melt blending method. The TPNR composites have been made with carbon fibers with random planar orientation both with treated and untreated with 1M sulfuric acid. The effect of surface treatment on the carbon fibre, strain rate and temperature on mechanical properties of the composites at various fibre loading (10%-40%) was investigated. It was found that the tensile properties of surface treated carbon fibre TPNR composite increased linearly with fiber concentration and decreased as temperature increased. The tensile stress also increased linearly with strain rate from 10-3 to 10-1 S-I. SEM micrograph on the fractured surface has shown that the sulfuric treated fibre had improved the fiber-matrix adhesion of TPNR